Assessing the socio-economic burden of inherited and inflammatory neuromuscular diseases (BIND study): a study protocol - Ian C. Smith; Yasmin Abusetah; Homira Osman; Aditi Garg; Alyssa Grant; Hanns Lochmuller; Hugh McMillan; Gerald Pfeffer; Lawrence Korngut; Cynthia Gagnon; Stacey Lintern; Daria Wojtal; et al. (Orphanet Journal of Rare Diseases)
Abstract Introduction Neuromuscular diseases (NMDs) are rare multisystem, genetic or acquired disorders causing weakness and/or sensory loss. It is essential for governments, insurance providers, and broader society to have a better understanding of the burden of illness of NMDs. Our goal is to assess the social and economic burden of Canadians living with NMDs, encompassing schooling and education achievement, health-related quality-of-life, and labour force participation and productivity. Methods and analysis We will conduct a national, cross-sectional survey of individuals living with a NMD and their caregivers who are members of Muscular Dystrophy Canada and/or are patients within our national network of neuromuscular clinics. Surveys can be completed online or via telephone. The specific sub-sections of the questionnaire will differ based on respondent’s profile, whether they are 1) a minor living with a NMD, 2) an adult living with a NMD, 3) an adult who is a caregiver for someone living with a NMD, or 4) an adult who both lives with a NMD and is a caregiver for someone with a NMD. We will use descriptive statistics to describe distributions and ranges of the social and economic measures. Pearson correlations for continuous data and Spearman rho for rank data will be used to detect the strength of association of socio-demographic factors, disease characteristics, and social and economic impacts of NMDs. Ethics and dissemination The study protocol has been approved by the Ottawa Health Science Network Research Ethics Board (Protocol ID # 20210601-01H). This study will provide the overall impact of NMD on costs and health-related quality of life, disseminated via a series of manuscripts which will include both between- and within-NMD/NMD subtype comparisons. The data obtained will guide governmental policy development and inform patient organisation programs to deliver more effective supports to individuals and families affected by NMDs.